Artefacts at the liquid interface and their impact in miniaturized biochemical assay - Litten, Brett (Biomicrofluidics, 2015)
Droplet microfluidic technology has the potential to significantly reduce reagent use, and therefore, lower costs of assays employed in drug discovery campaigns. In addition to the reduction in costs, this technology can also reduce evaporation and contamination which are often problems seen in miniaturized microtitre plate formats. Despite these advantages, we currently advise caution in the use of these microfluidic approaches as there remains a lack of understanding of the artefacts of the systems such as reagent partitioning from droplet to carrier oil and interaction of the biological reagents with the water-oil interface. Both types of artefact can lead to inaccurate and misleading data. In this paper, we present a study of the partitioning of a number of drug-like molecules in a range of oils and evidence of protein binding at the water-oil interface which results in reduced activity of a cytochrome P450 enzyme. Data presented show that the drug-like molecules partitioned the least into fluorocarbon oils and the interaction of the 1A2 cytochrome at the water-oil interface resulted in a lower or complete absence of enzyme activity. This loss of activity of cytochrome 1A2 could be restored by the use of secondary blocking proteins although changes in the pharmacology of known 1A2 inhibitors were observed. The artefacts described here due to reagents partitioning into the carrier oil or protein binding at the water-oil interface significantly impact the potential use of these microfluidic systems as a means to carry out miniaturized biological assays, and further work is needed to understand the impact and reduction of these phenomena.